Microencapsulation Enhances the in vitro Antibacterial Activity of a Citrus Essential Oil - Ambrosio, Carmen M.S. (2020)
ABSTRACT Essential oils (EOs) have become a promising alternative to antibiotic use in animal breeding because of their biological properties. Citrus EOs, a by-product of citrus processing industries, could be a feasible alternative due to their vast production worldwide. Encapsulation techniques, such as microencapsulation, could enable EO application in animal feed, preserving EO bioactivity. This study analyzes the use of foodgrade polymers, chitosan and modified starch, for microencapsulation of a commercial citrus EO, Brazilian orange terpenes (BOT), by spray-drying. Physical properties characterization showed that the microencapsulated BOT (MB-OT) had a moisture content = 5.39 %, aw = 0.40 and bulk density = 0.42 g/mL. Overall, microparticles presented a slight irregular-spherical shape, with a mean diameter of 2.77 μm and high polydispersity. Encapsulation efficiency reached 61.17 %. Furthermore, the antibacterial activity results showed that MBOT exerted a higher activity on enterotoxigenic E. coli U21 (isolated from pig gut) than on Lactobacillus rhamnosus, thus presenting a selective antibacterial activity between the pathogenic and beneficial bacteria. Moreover, MBOT exerted a higher selective antibacterial performance than the raw BOT, meaning the antibacterial performance of the raw BOT was enhanced by encapsulation. This is probably because wall material besides protects the raw BOT against volatilization; it could have interacted in synergism with the raw BOT enhancing the antibacterial effect of the MBOT powder. Finally, limonene was detected as the major compound in BOT by polar/non-polar GC-MS. Therefore, the modified starch-chitosan matrix could result in advantageous to encapsulate BOT and turn feasible its application in animal feed.